Avaliação do uso terapêutico de extrato do fungo Trichoderma stromaticum na infecção experimental de camundongos C57BL/6 com Toxoplasma gondii - Sousa, Layane Alencar Costa Nascimento (2019)
Trichoderma is well known fungi by inhibit the growth and development of a variety of plant pathogens. The crude ethanolic extract of T. stromaticum (Ext-Ts) are able to decrease the growth of P. falciparum in infected human red blood cells and, increase the survival and prevent neurological signs of P. berghei-ANKA-infected mice. Toxoplasma gondii orally infected C57BL/6 mice develop an inflammatory immune response in the small intestine that depending on the parasite load can lead to death in acute phase or toxoplasmic encephalitis in chronic phase. The most common treatment of toxoplasmosis is based in a combination of sulfadiazine and pyrimethamine, however, numerous collateral side effects have been described. Thus, the aim of this study was to verify the effect of treatment with ExtTs in oral T. gondii-infection of C57BL/6 mice. For this purpose, animals were infected with T. gondii, treated daily with ExtTs, and clinical, biochemical and histological features were monitored. It was observed that the ExtTs-treatment was able to decrease the parasitism and inflammation in the small intestine and liver in acute phase and parasitism in the brain in chronic phase of infection. Additionally, the ExtTs-treatment prevented the increase of lipid fractions systemically which are important for the parasite growth.